2021
DOI: 10.3390/acoustics3030033
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Sonic Environment and Noise Mitigations during the COVID-19 Pandemic Era

Abstract: The pandemic has impacted every facet of our life, society, and environment. It has also affected both the requirement and challenges for acoustic research and applications. The present article attempts to present a summary of the impact of COVID-19 on several aspects of acoustics, from the changes in the sonic environment due to reduced human and industrial activities to natural ventilation requirements for mitigating the transmission of coronavirus while mitigating noise, and, more importantly, discusses the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In particular, among all the environmental variations observed since the onset and development of the pandemic, sudden changes in noise levels (especially in urban contexts) were reported from different sources around the world (see for instance: [6][7][8][9][10][11]). In the environmental acoustics and soundscape research communities, this led to a growing interest to characterize changes in the sound environment of cities, both objectively (i.e., via acoustic measurements) and perceptually (i.e., via socio-acoustic surveys or alike) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, among all the environmental variations observed since the onset and development of the pandemic, sudden changes in noise levels (especially in urban contexts) were reported from different sources around the world (see for instance: [6][7][8][9][10][11]). In the environmental acoustics and soundscape research communities, this led to a growing interest to characterize changes in the sound environment of cities, both objectively (i.e., via acoustic measurements) and perceptually (i.e., via socio-acoustic surveys or alike) [12].…”
Section: Introductionmentioning
confidence: 99%
“…During the French lockdown period, Munoz et al (2020), investigated a decrease in sound levels of 4 dB to 6 dB compared to the normal situation, i.e., before lockdown at monitoring stations with extremely dominant road traffic sound. The table shows the summarized data of reduced average sound levels at numerous places in the pandemic COVID-19 (Lee and Kumar, 2021). According to Mostafa et al (2021), the Egyptian government revealed that the environmental noise level in Egypt was dropped by around 75% during the period of lockdown.…”
Section: Assessing T H E Effect O F Lockdown O N Noise Pollutionmentioning
confidence: 99%
“…A search in Web of Science (All fields: OF-FICE and PANDEMIC and ACOUSTICS, and Year published: 2020-2023; search April 2023) shows only fifteen results for this topic. Even just four of them are dealing with acoustics in detail, although not always with office acoustics: [5][6][7][8]. Thus, an extensive description on office acoustics and occupants' perception in post-pandemic offices is needed.…”
Section: Introductionmentioning
confidence: 99%